Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Peluang Berdasarkan Self-Regulated Learning (S-RL) - Azizah Azizah; Maimunah Maimunah; Yenita Roza (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
This is a case study to describe students' mathematical problem-solving abilities based on the level of independent learning on the probability chapter. The research subjects were ten students of MAN 1 Indragiri Hilir consist of two students for each level, which were very low, low, medium, high, and very high. Data collection uses problem-solving tests, questionnaires, and unstructured interviews. The results of Polya's problem-solving on the probability chapter are the high category for very high independence learner, the medium category for high and medium independence learner, and the low category for low and very low independence learner. The step of Polya's problem-solving which is not done optimally by each student of independent learning is verification (look back) the process and answer the question.